Dynamics of indicators of physical fitness and economy as a factor of sports results of high-class biathlonists - Myakinchenko, P. E.; Adodin, A. V.; Myakinchenko, E. B. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to study the dynamics of indicators of physical fitness and economy in the context of differences in the characteristics of the competitive activity of high-class biathletes.